Depiction Jinadatta Suri reviving a Mughal prince - Temples of India Project Team (Jio Institute, 2024)
As per the inscription on the fifteenth oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall), it depicts Jinadatta Suri reviving a Mughal prince. The story, commonly told in Jain traditions, recounts that once a Mughal prince fell from a horse and died. Jinadatta Suri commanded Vyantar Dev (forest celestial beings) to enter the dead prince’s body and bring him back to life. The Mughal prince is shown sleeping on a charpahi (four-legged bed) in the courtyard of the haveli (mansion). In the background, several buildings are depicted, suggesting a city settlement. Some of these buildings exhibit European architectural designs. The inscription reads, ‘Shri Jinadatta Suri Ji mugal putar ji la yo.’